Physico-chemical and sensorial properties of alpha-amylase treated puto (steamed rice cake) - Pedregoza, Joe Rey C. (2000.)
The effectivity of alpha-amylase to improve the texture of a steamed rice cake was tested.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Sensory evaluation; Alpha-amylase.; Puto; Rice cake--Steamed.